Markowitz Portfolio Learning Design in Financial Mathematics with Technology-Based Stock Investment Simulation Practice - Saputra, Moch Panji Agung; Saputra, Renda Sandi; Laksito, Grida Saktian (International Journal of Research in Community Services, 2025)
In an era of global economic uncertainty, mastering the concept of portfolio management is important for students in preparing themselves to face the challenges of the financial world. This study aims to design financial mathematics learning by integrating Markowitz's portfolio theory and technology-based stock investment simulation practices. The approach used includes the use of digital platforms to obtain historical stock data and stock market simulations for virtual investment practices. The results of the study indicate that the use of this method can improve students' understanding of the concepts of diversification, expected returns, and risk management in investment portfolios. With an interactive and practical approach, students can gain direct experience in building an optimal portfolio based on the Markowitz mean-variance model and implementing it in stock investment simulations. This study makes a significant contribution to the development of students' financial literacy by utilizing digital technology effectively.